FINANCIAL FLEXIBILITY OF IRAQI COMMERCIAL BANKS IN THE FACE OF MONETARY AND REGULATORY SHOCKS FOR THE PERIOD (2021-2025) (World Economics and Finance Bulletin, 2026)
This research aims to analyze the impact of monetary shocks (money supply, exchange rate) and regulatory shocks (capital adequacy) on the financial flexibility of Iraqi commercial banks during the period 2021-2025. The research is based on a quantitative methodology using sample panel data from Five representative banks, employing the tools of descriptive statistics, correlation analysis and multiple linear regression model via SPSS software. The theoretical framework is based on the theory of institutional flexibility in the context of the rentier Iraqi economy, which suffers from sharp fluctuations in the money supply associated with oil revenues.